German unification: A progress report - Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
In the five years after unification, efforts to bring up the eastern part of Germany to the level of the western one have made considerable progress. Eastern Germany's growth is moving towards the double digits, just like growth in the Pacific Rim region. But not all things have developed as well as they might. Rapid wage convergence has caused enormous unemployment in the east and a heavy tax burden in financing massive transfer payments in the west. The paper analyses the catching up of the eastern German economy against the background of the unpleasant trade-off between the pace of wage increase and the level of transfer payments necessary to spur investment and to finance consumption. It describes - first, the two-pronged policy mix to reconstruct and modernize the eastern German economy on a firm level, and, - second, typical adjustment profiles for the economy as a whole with regard to capital stock, output, and employment. Finally, it discusses the key policy question of how the high unemployment as well as the high costs of public assistance could be reduced.
Keywords: P52; 330; Nationale Einheit; Deutschland